Gender-based violence among women who use drugs: A quantitative and qualitative study in 6 EU countries (2023)
INTRODUCTION: The prevalence of gender-based violence (GBV) among women who use drugs (WWUD) is reportedly two to five times higher than among those who don’t use. This study aimed to analyse GBV experienced by WWUD in 6 EU countries. METHODS: A survey was carried out with 261 WWUD, and additionally, 492 professional staff working with WWUD were surveyed. Fifteen focus groups with WWUD and staff and 120 interviews with staff and key informants were also conducted. RESULTS: WWUD reported a high lifetime prevalence of GBV (97.69%) of all types and in many contexts. Migrant, ethnic minorities, and low-income WWUD seem to experience even more GBV. Eighty-six per cent (86.22%) among WWUD experienced violence at the hands of men who were using alcohol or drugs. They also reported aggression from men who do not use drugs (51.97%). Structural violence against women is the main factor explaining GBV. GBV is further exacerbated when alcohol and drugs are involved. Only 18.4% (n = 46) of WWUD and 25% (n = 115) of the staff reported that the “early detection systems and protocols for GBV” defined the service they were working in. Fifty-four per cent (54.39%; n = 267) of the staff acknowledged the need to improve their knowledge about the intersection between drug use and GBV. CONCLUSIONS: WWUDs are confronted with a high prevalence of different types of GBV in various settings. However, WWUD and staff surveyed have pointed to the lack of systematic screening for GBV in drug services. This poses a barrier to access and success in treatments and re-victimisation by the staff. The authors suggest specific training for professionals on drug use and GBV as a must, establishing protocols for systematic screening of GBV, and incorporating gender intersectional perspectives in drug services.